2017
DOI: 10.1038/s41598-017-12181-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between karst terrain and bauxites: evidence from Quaternary orebody distribution in Guangxi, SW China

Abstract: Most bauxite in China is located upon the karst surface, yet the relation between karstification process and bauxite formation is barely known. Here we discuss how the relation affects the karst and bauxite evolution through analyzing distributions of orebody parameters from 9,007 exploration wells (434 orebodies) in western Guangxi, South China block. In high-elevation karst terrain dominated by peaks, orebodies have greater average thickness, lower Al2O3 and higher Fe2O3 T than those in low-elevation region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Recent works successfully showed that the mineralogy of and geochemistry of REE can be controlled by the variation of pH and Eh [38], which can occur during several ore-forming stages that characterize the genesis of karst bauxites [38,48]. For example, in the Permian Longhe and Tianyang bauxite deposits (China) the in situ bauxitization was characterized by an alkaline and oxidizing environment (7 < ph < 10, −0.8 < Eh < 0, [42,49]).…”
Section: Genetic Processmentioning
confidence: 99%
“…Recent works successfully showed that the mineralogy of and geochemistry of REE can be controlled by the variation of pH and Eh [38], which can occur during several ore-forming stages that characterize the genesis of karst bauxites [38,48]. For example, in the Permian Longhe and Tianyang bauxite deposits (China) the in situ bauxitization was characterized by an alkaline and oxidizing environment (7 < ph < 10, −0.8 < Eh < 0, [42,49]).…”
Section: Genetic Processmentioning
confidence: 99%
“…Bauxite deposits that occur in limestones have been defined as karstic deposits, regardless of their parent rocks (Patternson, 1967;Bárdossy, 1982;Bardossy and Aleva, 1990). On the other hand, bauxite deposits that overlay alumosilicate rocks and were formed by their in situ lateritization are called laterite-type or silicate-type deposits (Bardossy and Aleva, 1990;D'Argenio and Mindszenty, 1995;Öztürk et al, 2002;Liu et al, 2010;Wang et al, 2011;Yu et al, 2014;Mongelli et al, 2016;Zamanian et al, 2016;Liu et al 2016;Torro et al, 2017;Yang et al;. As can be seen from the above classification, while lateritic-type or silica-type bauxite classification depends on the parental rock, the karstic-type is independent of the source rock.…”
Section: Comparison With World Bauxitesmentioning
confidence: 99%
“…Bauxite, a typical exogenous mineral resource, is formed by intense chemical weathering in humid and hot areas [ 1 ]. Bauxite deposits formed on the paleokarstic surfaces of carbonates, which are considered carbonate bauxite [ 2 , 3 ], are often located 1–2 m below the surface, and therefore they are usually mined by opencast mining (strip mining) [ 3 ]. The large-scale opencast mining process directly destroys surface rock layers and vegetation [ 4 ], leading to changes in the physical structure and loss of soil organic matter [ 5 ], drastically reducing the soil nutrient contents [ 6 ] and causing serious ecological damage [ 7 ].…”
Section: Introductionmentioning
confidence: 99%